Precipitador eletrostático: influência das condições operacionais e dos eletrodos de descarga na eficiência de remoção de nanopartículas - Andrade, Raíssa Gabrielle Silva Araújo (2020)
The industrial activities are the main cause of the particulate material emission, which results in the elevation of air pollution indices and respiratory diseases. One of the most common types of equipment to reduce emitted particle concentration in the atmosphere is the electrostatic precipitator, for its high versatility and for achieving high collection efficiency. Its operation consists of the air ionization containing the dispersed particles which will be electrically charged by the ions formed and attracted to the collecting electrodes, which reduces the particulate material concentration. The efficiency of electrostatic precipitation depends directly on the operating conditions and the geometrical characteristics of the equipment. In this context, the present study evaluated the influence of the operating conditions such as air velocity (1.03, 2.04 and 4.08 cm/s), electrical field (3.08-3.38 kV/cm) and discharge electrodes on NaCl nanoparticles removal efficiency. The electrostatic precipitator used was a single-stage wire-plate type, with two collecting plates with a height and length of 10 and 30 cm, respectively, spaced 6.5 cm apart. The studies were conducted in 3 steps, step 1 consisted of the discharge electrode number variation (1-4), with a wire diameter of 0.4 mm, spaced apart in 6.5 cm, with NaCl solution concentration of 0.1 and 0.5 g/L. In step 2, the configurations that presented the lowest collection efficiency in step 1 (1 and 2 wire experiments) were selected to compare the results obtained with the experiments performed with a new wire diameter, 0.3 mm, spaced at 6.5 cm. In step 3, the effect of increased wire spacing was analyzed, and the results of the experiments carried out in the previous 2-wire discharge steps, with wire diameters of 0.3 and 0.4 mm, were compared to the obtained data. for both wire diameters, with the new 12 cm spacing. The results proved the precipitator's efficiency in removing nanoparticles and evidenced the negative effect of the velocity increase in particle collection. The electrical field improved the collection efficiencies, due to the higher electric currents. Also, reducing the number of discharge wires impaired particulate collection in most experiments, as fewer emitters reduce the generated electrical current. The data obtained with the wire diameter of 0.3 mm proved the positive effect of the wire diameter reduction in the precipitator efficiency, as well as the increase in the discharge wire spacing. The results were used to determine the most predominant forces in the phenomenon of electrostatic precipitation, for the operating conditions used. From the obtained data, it was identified that the electric forces exerted a greater influence on the particle collection, which was intensified with the increase of the electrical field. In some cases, the same behavior occurred with an increasing number of wires. In contrast, the increase in velocity increased the action of viscous forces. Thus, the data collected showed that the best efficiencies were obtained for the lowest speed, along with the largest electric field, 3.38 kV/cm, and the best performance configuration used 4 discharge wires, with a concentration of 0.1 g/L with 99.99% removal. Finally, a statistical analysis was performed with the main operating conditions of each step, from which it was possible to prove the significant effect of the number of wires and the diameter of the wires, in steps 1 and 2. However, the data analysis of the step 3 showed that the wire spacing was not significant for the 3.08 and 3.38 kV/cm electric fields and had a very small positive effect for the 3.08 and 3.23 kV/cm electric fields.